Economy-wide Implications of Low Carbon Electricity Based Mass Transport in Nepal - Shakya, Shree Raj (Journal of the Institute of Engineering, 2014)
Development of low carbon electricity based mass transport is considered as one of the promising options for perusing the low carbon development (LCD) path in 21st century by the global communities. But long term economy-wide implications of such policy is very much country specifics citing their variations in the availability and tapping potential of indigenous clean energy resources, access to the clean technologies, affordability and acceptability of such technologies, and so on. This paper studies the economy-wide consequences of introducing different levels of electrified mass transport systems in Nepal on the long term basis. The study develops and uses a multi-sector, single region, recursive dynamic computable general equilibrium model of Nepal (Nepal-TRNSCGE) with technology level disaggregation in the transport and electricity sectors. The study indicates that under transport electrification scenarios consisting of 10% to 30% electrification of the transport sector as compared to the base case by 2050, the country would benefit economically with the value of cumulative undiscounted GDP increasing in the range of 2.6% to 3.1% and the value of cumulative undiscounted equivalent variation in income (household welfare) increasing in the range of 25.3% to 147.9% during 2005 to 2050. The policy would promote energy efficiency improvement and cleaner economic development with significant reduction in the energy intensity of GDP in the range of 3.1% to 4.1% and greenhouse gas intensity of GDP in the range of 4.7% to 7.1%. This highlights the potential role of low carbon electricity based transport in achieving the LCD path in the country. Introducing foreign direct investment would further increase GDP but reduce household welfare. DOI: http://dx.doi.org/10.3126/jie.v9i1.10679 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 142–165